Treatment of biliary cysts of the liver and polycystic liver disease: a surgical view - M. P. Kochieva; N. N. Bagmet; A. G. Abdullayev; O. G. Skipenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the review. To present up-to-date management approach to biliary cysts of the liver and polycystosis.Original positions. Opinions of surgeons differ in the issue of whom and when to operate, as well as in the choice of intervention procedure. At polycystosis, patients with the II type liver cysts (by J.Gigot classification) are exposed to treatment. At the presence of cysts of the III type, when the massive lesion of parenchyma takes place (>70%), there is no alternative for liver transplantation. At present there is no uniform medical approach in relation to diameter of cysts that results in application of various methods of treatment. Following variants are defined: 1) percutaneous puncture and drainage of cysts with injection of sclerosing agents; 2) laparoscopic erasion of free walls of cysts with impact on remaining epithelium; 3) erasion of cysts by laparotomic access. Laparoscopic resection of cysts is considered to be the optimal method that is low traumatic, with low frequency of relapses (0–4%) and minimum duration of hospital stay.Conclusion. Only 5–10% of patients with not parasitic (biliary) cysts of the liver are subject to surgical treatment, the others should be observed either by gastroenterologist, or by surgeon of out-patient department.